Environmental index for fragmentation impact and environment evolution analysis. Issue 2 (June 2022) - Rossi, A.; Vellutini, E.; Alessi, E.M.; Schettino, G.; Ruch, V.; Dolado Perez, J.C.
Highlights: Novel index for assessing the severity of a fragmentation. Tailoring of the index to specific size of the fragments. Tailoring of the index to specific surveillance network sensors. Abstract: Building on the definition of the Criticality of Spacecraft Index (Rossi et al., 2015) and of the Shell Criticality (Bombardelli et al., 2017), a procedure and an index able to quantify and visualize the medium term effects on the environment of a fragmentation in Low Earth Orbit is derived. The index takes into account the change in the environment caused by the fragmentation of a given mass in a specific orbit by quantifying the contribution of the fragments with respect to the original situation where the whole fragmented mass was contained in the intact objects. The index is devised in the frame of added-value SST services, as the fragmentation detection and impact evaluation service. Thus, weighting factors are included in its formulation to highlight the contribution of the untrackable debris created in the event. The index is applied and tested on four simulated fragmentations. The results show that the index is able to characterize the perturbation to the environment due to the cloud of fragments and its temporal evolution. Further work is ongoing to define the best values of the parameters in the model and of the weighting factors. A comparison with the results of the long term evolution models is also planned to assess the time limit validity of the representation given by the index.